KAJIAN FENOMOLOGIS ANGGARAN BERBASIS KINERJA PADA RUMAH SAKIT BAPTIS BATU - Yogivaria, Doni Wirshandono; Alfinur, Alfinur (Jurnal Ekonomi Modernisasi, 2016)
This study aims to understand the performance based budgeting at the Hospital  Private Sectors in batu. the subjects of this internship report consist of budgeting process included planning, performance measurement and evaluation, and reporting. besides, this internship also describes problems in budgeting process.  because of qualitative research, data was set by natural condition. The technique of collecting data was done by observation, interview and documentation study. the result of data compiler was analyzed by using qualitative methods that developed based on descriptive paradigm. the approach of phenomenology analysis used to describes comprehensive. Findings of this research showed that in general, the idealism of performance based budgeting is  achieved, although there is right in understanding of performance budgeting meaning by staff and managers.  there are many in budgeting process sequences included planning.